Improving Reading Comprehension of Middle and High School Students
X, 197 p. 3 illus., 2 illus. in color.
Keywords: This volume focuses on our understanding of the reading comprehension of adolescents in a high stakes academic environment. Leading researchers share their most current research on each issue, covering theory and empirical research from a range of specializations, including various content areas, English language learners, students with disabilities, and reading assessment. Topics discussed include: cognitive models of reading comprehension and how they relate to typical or atypical development of reading comprehension, reading in history classes, comprehension of densely worded and symbolic mathematical texts, understanding causality in science texts, the more rigorous comprehension standards in English language arts classes, balancing the practical and measurement constraints of the assessment of reading comprehension, understanding the needs and challenges of English language learners and students in special education with respect to the various content areas discussed in this book. This book is of interest to researchers in literacy and educational psychology as well as curriculum developers.